Progressive Microstructural Deterioration Dictates Evolving Biomechanical Dysfunction in the Marfan Aorta - Cavinato, Cristina; Chen, Minghao; Weiss, Dar; Ruiz-Rodríguez, Maria Jesús; Schwartz, Martin A.; Humphrey, Jay D. (Frontiers in Cardiovascular Medicine, 2021)
Medial degeneration leading to thoracic aortic aneurysms arises from multiple causes, chief among them mutations to the gene that encodes fibrillin-1 and leads to Marfan syndrome. Fibrillin-1 microfibrils associate with elastin to form elastic fibers, which are essential structural and functional components of the normal aortic wall. Compromised elastic fibers adversely impact overall structural integrity and alter smooth muscle cell phenotype. Despite significant progress in characterizing clinical, histopathological, and mechanical aspects of fibrillin-1 related aortopathies, a direct correlation between the progression of microstructural defects and the associated mechanical properties that dictate aortic functionality remains wanting. In this paper, age-matched wild-type, Fbn1C1041G/+, and Fbn1mgR/mgR mouse models were selected to represent three stages of increasing severity of the Marfan aortic phenotype. Ex vivo multiphoton imaging and biaxial mechanical testing of the ascending and descending thoracic aortas under physiological loading conditions demonstrated that elastic fiber defects, collagen fiber remodeling, and cell reorganization increase with increasing dilatation. Three-dimensional microstructural characterization further revealed radial patterns of medial degeneration that become more uniform with increasing dilatation while correlating strongly with increased circumferential material stiffness and decreased elastic energy storage, both of which comprise aortic functionality.